Synthesis and Fungicidal Evaluation of Some 1,3,4-Thiadiazoles against P. oryzae and R. solani - Yadav, L.S.; G.H. Zaidi, Mohd.; Singh, B.N. (Asian Journal of Chemistry, 2010)
A series of 2-amino-5-[(substituted phenoxy methylene)] -1,3,4- thiadiazoles from cresols, 2/4-chlorophenols and 4-chloro-3-methyl phenols have been synthesized. All such thiadiazoles have shown moderate activity towards the mentioned fungi.